Organic matter geochemistry and petrography of Late Cretaceous (Cenomanian-Turonian) organic-rich shales from the Belle Fourche and Second White Specks formations, west-central Alberta, Canada. (August 2015) - Furmann, Agnieszka; Mastalerz, Maria; Brassell, Simon C.; Pedersen, Per Kent; Zajac, Nicholas A.; Schimmelmann, Arndt
Highlights: Upper Belle Fourche Fm. contains kerogen Type II, not Type III as reported earlier. Prevalence of short-chain n -alkanes ( n -C13 to n -C19 ) in extracts of both formations. Minor concentrations of oleanane in extracts and low content of terrestrial vitrinite. Dominance of C28 and C27 steranes over C29 steranes in extracts of all samples. Abstract: Organic-rich mudstones with up to 10 wt% TOC from the upper portion of the Belle Fourche Formation and the lower part of the Second White Specks Formation in the Western Canada Sedimentary Basin were evaluated as source rocks. Both geochemistry and organic petrography indicate an open marine paleoenvironment with deposition of Type II kerogen based on the predominance of marine alginite and amorphous organic matter (OM), limited amounts of terrigenous vitrinite and inertinite macerals, the presence of marine fossils, and the low ratio of TOC to total sulfur (∼1.26). The prevalence of short-chain n -alkanes ( n -C13 to n -C19 ), a predominance of C28 αββ(H)-20S steranes, and small concentrations of oleanane confirm the dominantly algal and planktonic origin of OM. Alternating oxic to anoxic paleoenvironmental sedimentary conditions are proposed based on common bioturbation, abundant inoceramid prisms, and good organic richness. Biomarker distributions are consistent with intermittent anoxia, without unequivocal evidence for water column stratification or hypersalinity. The thermal maturity measured in seven sediment cores by different methods consistently indicates a westward increase in maturity according to vitrinite reflectance, T max, and hopane and sterane biomarkers. Two cores are thermally immature (∼0.42 %Ro), one is early mature (∼0.65 %Ro), and four cores are within the oil window (∼0.78 to 0.89 %Ro). All thermally mature cores retain good to very good hydrocarbon potential (248 mg HC/g rock) and are dominantly oil-prone and minor gas-prone based on their maceral compositions. The upper Belle Fourche and lower Second White Specks Formations represent potential targets for unconventional light shale oil production.